ANALISISPERSEPSIKONSUMENTERHADAPPELAYANANKARAOKEINULVIZTAFAMILYOUTLETCABANGKOTAJAMBI THEANALYSISOFCONSUMERPERCEPTIONONINULVIZTAFAMILYKARAOKESERVICEOUTLETOFJAMBIOUTLET - Aswadi Rahmad (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2012)
ThepurposeofthisresearchistoexplainconsumerperceptiononKaraokeInulViztaOutletinJambi.Thevariablemeasuredisbasedon5dimensions,i.e.,Tangibels,Realibility,Responsiveness,Assurance,Emphaty.Theresultshowsthatconsumerperceptionisgood.ThehigestvalueofperceptionisEmphatyDimensionandotherwisethelowestisAssurance.Accordingtotheresearchresuts,isreccomendedthatKaraokeInulViztaOutletcontinuestododevelopephysicaldimensionsuchasfasilitiesandphysicalinsfrastructures,trust,speed,prudishness,ability.Togehthertothisimprovement,itisimportanttobedovotedonconsumersatisfationmonitoring.Keyword:perception,Karaoke,consumerperceptions,services,